Mesospheric anomalous diffusion during noctilucent cloud scenarios - F. I. Laskar (Atmospheric Chemistry and Physics, 2019)
The Andenes specular meteor radar shows meteor trail diffusion rates increasing on average by about 10 % at times and locations where a lidar observes noctilucent clouds (NLCs). This high-latitude effect has been attributed to the presence of charged NLC after exploring possible contributions from thermal tides. To make this claim, the current study evaluates data from three stations at high, middle, and low latitudes for the years 2012 to 2016 to show that NLC influence on the meteor trail diffusion is independent of thermal tides. The observations also show that the meteor trail diffusion enhancement during NLC cover exists only at high latitudes and near the peaks of NLC layers. This paper discusses a number of possible explanations for changes in the regions with NLCs and leans towards the hypothesis that the relative abundance of background electron density plays the leading role. A more accurate model of the meteor trail diffusion around NLC particles would help researchers determine mesospheric temperature and neutral density profiles from meteor radars at high latitudes.